Isolated tuberculoma involving multiple paranasal sinuses with aggressive features in an immunocompetent individual masquerading as a malignant neoplasm: A rarity unveiled with review of literature - Shaivy Malik; Rajat; Charanjeet Ahluwalia (IDCases)
Isolated primary tuberculoma of the paranasal sinuses is an exceedingly rare form of extra-pulmonary tuberculosis (EPTB), particularly in immunocompetent individuals. Its presentation is often atypical, mimicking aggressive neoplasms due to features such as local bone destruction, which complicates diagnosis and may lead to unnecessary invasive interventions. We report the case of a 32-year-old immunocompetent male presenting with chronic right nasal obstruction, rhinorrhoea, facial puffiness, hyposmia, and intermittent fever. Imaging revealed a heterogeneous mass in the right frontal, ethmoidal, and maxillary sinuses, with extensive bony erosion suggestive of a malignant etiology. Histopathological examination of biopsy tissue, however, demonstrated granulomatous inflammation with Langhans giant cells, necrosis, and acid-fast bacilli on Ziehl-Neelsen staining, confirming tuberculoma. Anti-tubercular treatment (ATT) was promptly initiated post-biopsy, leading to complete symptom resolution and no recurrence. This case sheds light on the importance of including tuberculoma in the differential diagnosis of aggressive sinonasal lesions in immunocompetent patients despite their rarity, and highlights the critical role of histopathology and ATT in effective management, potentially preventing extensive surgical resections and associated morbidity.